A Comparative Study of Menstrual Hygiene Issues between Public and Private School Going Adolescent Girls in Kathmandu Valley - Pandey, Ashok; Mahotra, Narayan Bahadur (Journal of Manmohan Memorial Institute of Health Sciences, 2019)
Introduction: Menstruation is part a of the female reproductive cycle that starts when girls become sexually mature at the time of puberty. During menstrual period, woman bleeds from her uterus via the vagina. Menstruation is generally considered as unclean in our Nepali society. So, good hygienic practices such as the use of sanitary pads and adequate cleaning of the genital areas are essential during menstrual period.Material and methods: The comparative study was carried out with adolescent girls studying in public and private schools in Kathmandu valley. A total of 100 adolescent girls, 50 from public school and another 50 from private schools were selected for the study and 25 from each group were taken for quantitative study as well. Two focus group discussions and five key-in-depth interviews were also done to identify the qualitative findings. Ethical approval was taken from NHRC. Quantitative data from the survey was analyzed using SPSS 16.0 software.Results: The age of the respondents ranges from 11 to 18 years. The mean age at menarche was 12.37 years in both public and private school adolescent girls. There is a statistically significant difference on the overall score of practice during menstruation between public and private school going adolescent girls.Conclusion: Private school adolescent girls were more knowledgeable and maintain menstrual hygiene better as compared to public school adolescent girls.